Inequality in Germany: Myths, Facts, and Policy Implications - Michele Battisti; Gabriel Felbermayr; Sybille Lehwald (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2016)
In this paper we try to provide an overview of a series of simple descriptive facts onrecent trends in economic inequality in Germany. We believe that it is important to beprecise in the way in which we define the inequality measure and the sample we use, toavoid generating vague messages that fail to properly inform policy makers and thepublic. Using mostly administrative data from the IAB and panel survey data fromSOEP, we show that some of the conventional wisdom on recent trends on incomeinequality in Germany does not seem to find strong support in the data. In particular, wefind that current low levels of unemployment are likely to imply higher levels ofmeasured inequality among the employed, but are likely to diminish inequality amongthe working-age population as a whole. Our paper also discusses the importance tocarefully distinguish between inequality at the individual and household levels, andseparate the role of the welfare state. Finally, while admitting data limitations we brieflyanalyse recent trends in wealth inequality in Germany, and discuss the possible role ofrecent macroeconomic policies on wealth inequality.
Keywords: D31; D63; 330; Income inequality in Germany; Gini coefficient; Recentered Influence Function decomposition; compositional effects